WISATA “MANYAMABRAYA”: PAKET WISATA “AJEG BALI” BERBASIS LOCAL GENIUS - Komang Trisna Dewi; Widya Duta (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
This research is a qualitative research that aims to describe"manyamabraya" tourism based on local genius in the Mengali TraditionalVillage, Sawan-Buleleng District. The research data were collected usingdocumentation, interview, and observation techniques with researchinstruments in the form of interview guides and observation sheets. Thedata collected was then analyzed descriptively qualitatively by followingthe interactive analysis method proposed by Miles and Huberman (1994).This study concludes that, (1) "Manyamabraya" tourism based on localgenius in the Mengali Traditional Village is a tourism concept that providesthe opportunity for tourists to be directly involved in the socio-cultural lifeof the community in the Mengali Traditional Village, (2) This tour wasdeveloped because of the natural and cultural potential which is verysuitable to be developed into a cultural-based tourist destination, as wellas the weakness of the community's economy has encouraged creativeideas to develop this "manyamabraya" tourism, (3) The "manyamabraya"tourism is managed directly independently by the community of theMengali Indigenous Village, starting from providing accommodation,tourist activities, food, drinks and entertainment